Combinatorial Separation of Cd and Te from CdTe via Chemical Vapour Transport with Sulfur and Air/Methane Treatment for the Recovery of Critical Resources from Thin Film Solar Cells - Bemfert, Lucas H.; Burkhart, Julian; Sedykh, Alexander E.; Richter, Sophie; Mitura, Eliane L.; Maxeiner, Moritz; Sextl, Gerhard; Müller‐Buschbaum, Klaus (ChemSusChem, 2025)
Elemental Te and Cd are successfully recovered from CdTe via a combinatorial process involving chemical vapor transport (CVT) using sulfur as transport agent giving elemental Te being deposited. Separation is successfully enabled by the first process for CVT of Te starting with CdTe. Cd is subsequently recovered by an oxidation of the formed CdS to CdO followed by reduction to Cd metal with natural gas, in which Cd can also be separated via the gas phase. Hereby, the process addresses the main critical elements of the active material in thin film CdTe solar cells regarding both, scarcity and toxicity. Both, closed and open systems were investigated displaying more or less thermodynamic control of the system. Transport rates were determined for the closed system as well as for an open system working with sulfur vapour at moderate temperatures below and close to the boiling point of sulfur. Excellent purity of tellurium was achieved already by the initial transport, leading to low Cd2+ concentrations in the obtained Te being below the quantification limit of microwave plasma‐atomic emission spectroscopy (MP‐AES) (≪0.05 wt %). Recovery of the two critical elements Cd and Te from CdTe for recycling of solar cells was tested using chemical vapour transport of Te with S as transport agent at temperatures below the boiling point of S. Cd is also recovered via the gas phase by oxidation of CdS and reduction with methane.